Creating a Sustainable Community Forest Management Network Based on the Principles of HM’S Development Works in Lamphun Province - ๋Jindaluang, Kornravee; Wattanakul, Watcharapong; Suwan, Manut; Samphutthanont, Ratchaphon (Dhammathas Academic Journal, 2025)
This research aimed to analyze factors contributing to sustainable community forest management success using HM’s Development Works principles and proposed a model for establishing a network of community forest management in Lamphun Province. Data were collected from community leaders and community forest committee members at 7 locations. through document study, observation, interviews, participatory workshops, and a 5-point Likert scale questionnaire, then analyzed using descriptive statistics and t-tests. Results showed that Dong Huay Yen Community Lamphun Province, was recognized as a model for sustainable forest management, successfully applying 13 principles of HM’s Development Works. Emphasizing sufficiency, integrity, and participation, the community covered four dimensions: social, process, principles, and development, whereas other communities applied these principles to a lesser extent. Expert evaluation of the network model across all seven communities showed high suitability (4.70 ± 0.249), including economic and methodological appropriateness (4.56±0.387), feasibility of implementation (4.55±0.409), and alignment with HM’s Development Works (4.87 ±0.279). Community feedback on the model’s applicability also increased (3.66±0.611 compared to 3.92±0.541), though this difference was not statistically significant (P > 0.05). This study demonstrated that community forest management networks based on HM’s Development Works emphasizing community participation, learning, conservation, cooperation, honesty, Sufficiency Economy, and continuous improvement effectively supported communities in achieving sustainable forest management.